Zika Virus 101: A Mini Review - Nandini , N.; Deepthi , S.; Sindhu, M. (International Journal of Scientific Research and Management (IJSRM), 2023)
Zika virus is a mosquito-borne Flavivirus that is the focus of an ongoing pandemic and public health emergency. The Zika virus outbreak in Brazil in 2015, previously limited to sporadic cases in Africa and Asia, heralded a rapid spread across the Americas. Although most Zika virus infections are characterized by subclinical or mild flu-like illness, severe manifestations have been reported, including Guillain-Barre syndrome in adults and microcephaly in children born to infected mothers. There is no effective treatment or vaccine for the Zika virus; therefore, the public health response is primarily focused on preventing infections, especially in pregnant women. Despite the growing knowledge of this virus, questions remain regarding the vectors and reservoirs of the virus, pathogenesis, genetic diversity, and potential synergistic effects of coinfection with other circulating viruses. These questions highlight the need for research to optimize surveillance, patient management, and public health interventions in the current Zika virus epidemic .Zika virus (ZIKV) is an emerging arthropod-borne Flavivirus that leads to teratogenic effects and neurological disorders after infection. ZIKV infections are a serious global public health problem, leading scientists to increase research into antiviral and vaccines against the virus. These efforts are still ongoing, as the pathogenesis and immune evasion mechanisms of ZIKV are not yet fully understood. There are currently no specific vaccines or drugs approved for ZIKV; however, some are undergoing clinical trials. Notably, several strategies have been used to develop antiviral, including drugs that target viral and host proteins. In addition, drug reuse is preferred because it is cheaper and less timeconsuming than other strategies because the drugs used have already been approved for human use. Similarly, various platforms for vaccine design have been evaluated, including DNA, mRNA, peptide, protein, viral vectors, virus-like particles (VLPS), inactivated viruses, and live attenuated virus vaccines. These vaccines have been shown to induce specific humoral and cellular immune responses and reduce viremia and viral RNA in vitro and in vivo. Importantly, most of these vaccines have entered clinical trials. Understanding the mechanism of viral disease will provide better strategies for the development of therapeutic agents against ZIKV. This review provides a comprehensive summary of the viral pathogenesis of ZIKV and current progress in the development of vaccines and drugs against this virus.